2015
DOI: 10.1016/j.cja.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of endwall contouring in axial compressor S-shaped ducts

Abstract: This paper presents a numerical investigation of the potential aerodynamic benefits of using endwall contouring in a fairly aggressive duct with six struts based on the platform for endwall design optimization. The platform is constructed by integrating adaptive genetic algorithm (AGA), design of experiments (DOE), response surface methodology (RSM) based on the artificial neural network (ANN), and a 3D Navier-Stokes solver. The visual analysis method based on DOE is used to define the design space and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…With the assumption of uniform flow without swirl at all circumferential direction of the S-shaped duct inlet, a 3-D S-shaped duct can be represented well by the approach of 2-D axisymmetric. This will reduce complexity as well as computational time for convergence of the fluid domain [2,15,19,38,40,41]. Modeling and meshing of the 2-D axisymmetric S-shaped duct are accomplished by using 'GAMBIT' software.…”
Section: Geometry Creation Meshing and Case Formationmentioning
confidence: 99%
See 3 more Smart Citations
“…With the assumption of uniform flow without swirl at all circumferential direction of the S-shaped duct inlet, a 3-D S-shaped duct can be represented well by the approach of 2-D axisymmetric. This will reduce complexity as well as computational time for convergence of the fluid domain [2,15,19,38,40,41]. Modeling and meshing of the 2-D axisymmetric S-shaped duct are accomplished by using 'GAMBIT' software.…”
Section: Geometry Creation Meshing and Case Formationmentioning
confidence: 99%
“…Equation (18) calculates the new velocity V i+1 the individual particle by using the previous velocity, best location ('pBest') and obtained global best location ('gBest') into the entire population as well and at the same time, individual particle's location ( X i ) in the hyperspace is updated by the Eq. (19). In the Eq.…”
Section: Particle Swarm Optimization Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the scarcity of design guidelines and performance correlations of the annular S-shaped duct, to obtain a better design, CFD can be implemented as a design approach for performance evaluation with a combination of various optimization techniques [19]. Many researchers have reported that applying the response surface methodology (RSM) altogether with the design of experiments (DOE) may be a decisive and sturdy method for CFD-based optimization techniques [20][21][22][23]. In this field, the first work came from Wallin et al [20].…”
Section: Introductionmentioning
confidence: 99%